Sickle cell anemia: iron availability and nocturnal oximetry. - Cox, SE; L'Esperance, V; Makani, J; Soka, D; Prentice, A; Hill, C; Kirkham, F (2012)
STUDY OBJECTIVE: To test the hypothesis that low iron availability, measured as transferrin saturation, is associated with low nocturnal hemoglobin oxygen saturation (SpO(2)) in children with homozygous sickle cell anemia (SCA; hemoglobin SS). METHODS: This was a cross-sectional study of Tanzanian children with SCA who were not receiving regular blood transfusions. Thirty-two children (16 boys) with SCA (mean age 8.0, range 3.6-15.3 years) underwent motion-resistant nocturnal oximetry (Masimo Radical) and had steady state serum transferrin saturation and hematological indices assessed. RESULTS: Higher transferrin saturation, adjusted for age and α-thalassemia deletion, was associated with lower nocturnal mean SpO(2) (p = 0.013, r(2) = 0.41), number of SpO(2) dips/h > 3% from baseline (p = 0.008, r(2) = 0.19) and with min/h with SpO(2) < 90% (p = 0.026 r(2) = 0.16). Transferrin saturation < 16% (indicative of iron deficiency) was associated with a 2.2% higher nocturnal mean SpO(2). CONCLUSIONS: Contrary to our hypothesis, higher iron availability, assessed by transferrin saturation, is associated with nocturnal chronic and intermittent hemoglobin oxygen desaturation in SCA. Whether these associations are causal and are driven by hypoxia-inducible factor and hepcidin-mediated upregulation of demand for iron warrants further investigation.